Imagining Numbers - Barry Mazur (Penguin Books, 2004)
Mazur considers the range of our imaginative experiences, especially in relation to mathematics. When we imagine a number, in particular an impossible number such as the square root of a negative quantity, what imaginative object might this bring to mind?